Parametric study and uncertainty quantification of the nonlinear modal properties of frictional dampers - Sun,Y; Yuan,J; Pesaresi,L; Denimal,E; Salles,L (Journal of Vibration and Acoustics, 2020)
A numerical methodology is described to study the influ-ence of the contact location and contact condition of fric-tion damper in aircraft engines. A simplified beam model isused to represent the blade for the preliminary design stage.The frictional damper is numerically analysed based on twoparameters, contact angle and vertical position of the plat-form. The nonlinear modal analysis is used to investigatethe nonlinear dynamic behaviour and damping performancesof the system. Harmonic balanced method with continua-tion technique is used to compute the nonlinear modes for alarge range of energy levels. Using such a modelling strat-egy, modal damping ratio, resonant amplitude and resonantfrequency are directly and efficiently computed for a rangeof design parameters. Monte Carlo simulations togetherwith Latin hypercube sampling is then used to assess the ro-bustness of the frictional damper, whose contact parametersinvolve much uncertainties due to manufacturing toleranceand also wear effects. The influences of those two parame-ter are obtained and the best performances of the frictionaldamper can be achieved when the contact angle is around25-30. The vertical position of the platform is highlymode-dependent and other design considerations needs to beaccounted. The results have been proved that the uncertain-ties involved contact surfaces do not have significant effects∗Address all correspondence for other issues to this author.on the performance of frictional damper.